Efficient truss optimization using the contrast-based fruit fly optimization algorithm. (1st April 2017) - Kanarachos, Stratis; Griffin, James; Fitzpatrick, Michael E.
Highlights: Truss optimization using fruit fly optimization algorithm. Advanced modelling of fruit fly food search behaviour. Efficiency in truss optimization with frequency constraints. Intuitive, few tuning parameters. Abstract: A recent biological study shows that the extremely good efficiency of fruit flies in finding food, despite their small brain, emerges by two distinct stimuli: smell and visual contrast. "contrast-based fruit fly optimization", presented in this paper, is for the first time mimicking this fruit fly behaviour and developing it as a means to efficiently address multi-parameter optimization problems. To assess its performance a study was carried out on ten mathematical and three truss optimization problems. The results are compared to those obtained using twelve state-of-the-art optimization algorithms and confirm its good and robust performance. A sensitivity analysis and an evaluation of its performance under parallel computing were conducted. The proposed algorithm has only a few tuning parameters, is intuitive, and multi-faceted, allowing application to complex n-dimensional design optimization problems.